The Director–Composer Duo: Polanski & Komeda’s Deconstruction of Film Music Conventions in Horror Cinema. "Fearless Vampire Killers" (1967) and "Rosemary’s Baby" (1968) - Pomostowski, Piotr (Załącznik Kulturoznawczy, 2023)
This article looks at the relationship between music and image in the two final films that Roman Polanski made with Krzysztof Komeda. Fearless Vampire Killers and Rosemary’s Baby are cinematic examples of a very close collaboration between a director and a composer. The article deals with the function of music in relation to genre films. The most important question is the extent to which Krzysztof Komeda’s compositions adhere to or depart from the horror film music convention. A key issue in this context, and one that applies to both of the analyzed films, is the technique of leitmotifs which Polanski and Komeda developed already in their first short films. In Fearless Vampire Killers and Rosemary’s Baby, the jointly developed director-composer method evolved greatly, and Polanski’s collaboration with Komeda took on a very distinctive style, which the author of this article attempts to describe and define. The text is a translation of an excerpt from the chapter "Nieustraszeni zabójcy wampirów i Dziecko Rosemary, czyli filmowe wyzwanie dla jazzmana, który przestaje nim być” [The Fearless Vampire Killers and Rosemary’s Baby, or a film challenge for a soon-to-be ex-jazzman] in the book Reżyser na ścieżce dźwiękowej. Funkcje muzyki w twórczości filmowej Romana Polańskiego [The director on the soundtrack: functions of music in Roman Polański’s films] published by Wydawnictwo Naukowe UAM, Poznań 2018.